Impact of the COVID-19 Pandemic on COPD Patient Mortality: A Nationwide Study in France - Jonas Poucineau; Jonas Poucineau; Myriam Khlat; Nathanaël Lapidus; Nathanaël Lapidus; Nathanaël Lapidus; Maude Espagnacq; Christos Chouaïd; Christos Chouaïd; Tristan Delory; Tristan Delory; Tristan Delory; et al. (Frontiers Media S.A., 2024)
Objectives: We investigated the mortality patterns of chronic obstructive pulmonary disease (COPD) patients in France relative to a control population, comparing year 2020 to pre-pandemic years 2017-2019.Methods: COPD patient and sex, age and residence matched control cohorts were created from the French National Health Data System. Survival was analyzed using Cox regressions and standardized rates.Results: All-cause mortality increased in 2020 compared to 2019 in the COPD population (+4%), but to a lesser extent than in the control population (+10%). Non-COVID-19 mortality decreased to a greater extent in COPD patients (−5%) than in the controls (−2%). Death rate from COVID-19 was twice as high in the COPD population relative to the control population (547 vs. 279 per 100,000 person-years).Conclusion: The direct impact of the pandemic in terms of deaths from COVID-19 was much greater in the COPD population than in the control population. However, the larger decline in non-COVID-19 mortality in COPD patients could reflect a specific protective effect of the containment measures on this population, counterbalancing the direct impact they had been experiencing.